BTS Application: Online Thesis Consultation - Hardiyana, Bella (Universitas Komputer Indonesia, 2022)
The learning process at universities is hindered by the Covid-19 pandemic, so activities that should be carried out face-to-face must be done online. One of the activities that are hampered is thesis consultation. Thesis consultation should be done directly, face to face, and verified on the attendance card, and it cannot be carried out as usual. The consultation can only be done online by sending files to the supervisor and then reviewing the results of the work. However, by doing it online, it will not be easy to fill out the attendance card that must be signed in person. The signing process becomes online, by sending the digital version of attendance card to the supervisor, then be signed by the supervisor and sent again to the student. The purpose of this research is to design a thesis consultationinformation system in which everything is centralized and documented in one platform. This research usedqualitative descriptive analysis method and system development method using prototype. The results showed that the system design that was built could help become a medium for exchanging files between supervisors and students. The output of this system will be documented. The history of each counsel carried out will be recorded so that the attendance card will be filled automatically